Paulinian Remote Flexible Learning Experience (ReFLEx): Perceptions among Junior High School Students - Arpilleda, Alcher J. (Journal of Educational Research and Practice, 2025)
The COVID-19 pandemic necessitated a rapid shift to remote learning, posing unprecedented challenges for educational institutions worldwide. This study investigates the Paulinian Remote Flexible Learning Experience (ReFLEx) at St. Paul University Surigao, a program distinguished by its adaptive combination of synchronous and asynchronous learning, designed to maintain educational continuity and enhance student engagement. Employing an embedded mixed-methods approach, the research prioritizes quantitative data from 116 Grade 9 students while integrating qualitative insights from interviews with 10 purposefully selected informants. Findings indicate an overall very satisfactory assessment of ReFLEx, with teacher competence emerging as a particularly strong point (M=3.58, SD=0.56). However, the study reveals a statistically significant difference in ReFLEx assessment based on the respondent’s sex (z=-2.329, p = .020), suggesting nuanced gender-related experiences within the program. These results underscore the critical role of teacher training and sensitivity in blended learning environments and highlight the importance of considering demographic factors in program design. Practically, the study suggests targeted interventions to address disparities in student experiences and further enhance teacher support. Theoretically, it contributes to the growing body of knowledge on remote learning effectiveness, offering insights into the design and implementation of flexible educational models. The findings inform future planning and program development, supporting the refinement of ReFLEx and similar initiatives to optimize student learning outcomes in evolving educational landscapes.